2019
DOI: 10.7126/cumudj.502650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Finishing Methods and Aging on Surface Roughness and Optical Properties of Zirconia-Reinforced Lithium Silicate Glass-Ceramic

Abstract: Objectives: The effects of three different surface finishing methods and aging on the surface roughness and optical properties of zirconia-reinforced lithium silicate (ZLS) glass-ceramic were investigated. Materials and Methods: Rectangular specimens (0.6 mm thickness) were sliced from ZLS blocks (N=36). Three different types of surface finishing [glazing combined with crystallization (ZLS-CF) or after crystallization (ZLS-G) and polishing (ZLS-P)] (n=12) and 5000 thermocycles were applied. Three sets of measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…The lower TP of the VS group compared to E.max is mostly related to its composition and the addition of 10% zirconia particles in its matrix. Notably, the values recorded in this study were higher than the ones reported by Alp and Subaşi (12.9 ±0.59 at 0.6 mm) [22].…”
Section: Discussioncontrasting
confidence: 84%
“…The lower TP of the VS group compared to E.max is mostly related to its composition and the addition of 10% zirconia particles in its matrix. Notably, the values recorded in this study were higher than the ones reported by Alp and Subaşi (12.9 ±0.59 at 0.6 mm) [22].…”
Section: Discussioncontrasting
confidence: 84%
“…The smoothness, and the surface quality of the prosthetic material are important to achieve the desired aesthetic appearance and long-term clinical success [43], because rough surfaces affect discoloration and shade matching. Alp and Subaşı (2019) and Al-Hebshi et al (2005) assessed the effect of khat on salivary parameters and found that it caused inadequate and decreased salivary flow rate with high viscosity and lowered the pH of saliva. These factors were associated with increased risk of teeth discoloration [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Alp and Subaşı (2019) and Al-Hebshi et al (2005) assessed the effect of khat on salivary parameters and found that it caused inadequate and decreased salivary flow rate with high viscosity and lowered the pH of saliva. These factors were associated with increased risk of teeth discoloration [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lithium disilicate glass ceramic E-max CAD was chosen as a standard for comparison with ZLS ceramics because of its frequent use in many clinical and laboratory research papers (6,10,18) . Two ZLS (Celtra) ceramic materials with different restoration manufacturing techniques and surface finishing were also chosen as the processing method (19) and surface finishing (20) can affect the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thermocycling accompanied the wear simulation test did not maintain the uniform aspect of the glazed surface resulting in some defects (34) . According to the study of Alp and Subaşı, the surface roughness was increased with aging of the ZLS glass-ceramic and the type of surface finishing significantly affected the surface roughness (20) . However, the crystal size of milled Celtra Duo is smaller than that of heat pressed Celtra Press ceramic.…”
Section: Discussionmentioning
confidence: 99%